Clinical, Neuroimaging, and Genetic Markers in Cerebral Amyloid Angiopathy-Related Inflammation: A Systematic Review and Meta-Analysis. Issue 1 (1st December 2022) - Theodorou, Aikaterini; Palaiodimou, Lina; Malhotra, Konark; Zompola, Christina; Katsanos, Aristeidis H.; Shoamanesh, Ashkan; Boviatsis, Efstathios; Dardiotis, Efthimios; Spilioti, Martha; Sacco, Simona; Werring, David J.; Cordonnier, Charlotte; et al.
Abstract : Background: There are limited data regarding the prevalence of distinct clinical, neuroimaging and genetic markers among patients diagnosed with cerebral amyloid angiopathy–related inflammation (CAA-ri). We sought to determine the prevalence of clinical, radiological, genetic and cerebrospinal fluid biomarker findings in patients with CAA-ri. Methods: A systematic review and meta-analysis of published studies including patients with CAA-ri was conducted to determine the prevalence of clinical, neuroimaging, genetic and cerebrospinal fluid biomarker findings. Subgroup analyses were performed based on (1) prospective or retrospective study design and (2) CAA-ri diagnosis with or without available biopsy. We pooled the prevalence rates using random-effects models and assessed the heterogeneity using Cochran-Q and I 2 -statistics. Results: We identified 4 prospective and 17 retrospective cohort studies comprising 378 patients with CAA-ri (mean age, 71.5 years; women, 52%). The pooled prevalence rates were as follows: cognitive decline at presentation 70% ([95% CI, 54%–84%]; I 2 =82%), focal neurological deficits 55% ([95% CI, 40%–70%]; I 2 =82%), encephalopathy 54% ([95% CI, 39%–68%]; I 2 =43%), seizures 37% ([95% CI, 27%–49%]; I 2 =65%), headache 31% ([95% CI, 22%–42%]; I 2 =58%), T2/fluid-attenuated inversion recovery-hyperintense white matter lesions 98% ([95% CI, 93%–100%]; I 2 =44%), lobar cerebral microbleeds 96% ([95% CI, 92%–99%]; I 2 =25%), gadolinium enhancing lesions 54% ([95% CI, 42%–66%]; I 2 =62%), cortical superficial siderosis 51% ([95% CI, 34%–68%]; I 2 =77%) and lobar macrohemorrhage 40% ([95% CI, 11%–73%]; I 2 =88%). The prevalence rate of the ApoE (Apolipoprotein E) ε4/ε4 genotype was 34% ([95% CI, 17%–53%]; I 2 =76%). Subgroup analyses demonstrated no differences in these prevalence rates based on study design and diagnostic strategy. Conclusions: Cognitive decline was the most common clinical feature. Hyperintense T2/fluid-attenuated inversion recovery white matter lesions and lobar cerebral microbleeds were by far the most prevalent neuroimaging findings. Thirty-four percent of patients with CAA-ri have homozygous ApoE ε4/ε4 genotype and scarce data exist regarding the cerebrospinal fluid biomarkers and its significance in these patients.